1990
DOI: 10.1038/347306a0
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of ribonuclease H from E. coli

Abstract: The three-dimensional structure of RNase H from Escherichia coli was determined at 1.8 A resolution by X-ray crystallography. The enzyme was found to belong to the alpha + beta class of structures, consisting of two distinct domains. The structure implies a possible region interacting with a DNA-RNA hybrid. The Mg2(+)-binding site essential for activity is located near a cluster of four acidic amino acids--one glutamic and three aspartic acid residues. These residues are completely conserved in the homology al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
291
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(302 citation statements)
references
References 22 publications
10
291
0
Order By: Relevance
“…Although the primary amino acid sequence did not provide any clue to the function of PF2046, analysis of the structure of PF2046 by DALI, Profunc and CATH indicated that the secondary structural elements of PF2046 are similar to a RNase HI (Katayanagi et al, 1990;Davies et al, 1991;Ohtani et al, 2004). We analyzed the structure further for signature motifs and catalytic residues necessary for the processing of nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the primary amino acid sequence did not provide any clue to the function of PF2046, analysis of the structure of PF2046 by DALI, Profunc and CATH indicated that the secondary structural elements of PF2046 are similar to a RNase HI (Katayanagi et al, 1990;Davies et al, 1991;Ohtani et al, 2004). We analyzed the structure further for signature motifs and catalytic residues necessary for the processing of nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
“…3A). The carboxylic acids are known to bind metal ions in RNase HI (Katayanagi et al, 1990;Davies et al, 1991;Ohtani et al, 2004). In addition to the carboxylic acids, a histidine residue participates in the catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…A 12 bp RNA-DNA (59-32 P-cggagaugacgg-39, 39-GCCTCTACTGCC-59; note that ribonucleotides are shown by lower-case letters), 35 bp DNA-RNA-DNA/DNA (59-32 P-AGAGGCAGGAGAGTuGCAACGCAGCAAGAGGACGC-39, 39-TCTCCG-TCCTCTCAACGTTGCGTCGTTCTCCTGCG-59) and Ribo primer (59-32 P-GCGTCCTCTT GCTGCGTTGCaa-39, 39-CGCAGGAGAAC-GACGCAACGTTGAGAGGACGGAGA-59) were used as substrates. All oligonucleotides carrying ribonucleotide(s) were 59-end-labelled with 32 P and the hybrid duplexes were prepared by standard procedures (Katayanagi et al, 1990). The cleavage assays were performed in reaction mixture containing 0.2 mM of different ribonucleotide substrates and specified amounts of Cpn-RNase Hs.…”
Section: In Vitro Enzymic Activity Assaysmentioning
confidence: 99%
“…Although the crystal structures of some RNase HI and HII enzymes have been determined, e.g. E. coli (Katayanagi et al, 1990;Yang et al, 1990), Methanococcus jannaschii (Lai et al, 2000) and Thermoccus kadakaraensis (Muroya et al, 2001), little 3D structural information on RNase HIII is available. The enzymic properties of a few RNase HIIIs such as Bacillus subtilis RNase HIII and B. stearothermophilus RNase HIII have been analysed (Ohtani et al, 1999b;Chon et al, 2004Chon et al, , 2006a.…”
Section: Introductionmentioning
confidence: 99%
“…Among these RNases, RNase H (Crouch, 1990;Katayanagi et al, 1990) has been defined as an enzyme that specifically degrades the ribonucleotide moiety in RNA-DNA hybrid molecules (Ohtani et al, 1999a, b). RNases H are classified into two major families, type I and type II, which are evolutionarily unrelated.…”
Section: Introductionmentioning
confidence: 99%